2006
DOI: 10.1183/09031936.06.00019405
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-17 during acute rejection after lung transplantation

Abstract: Acute rejection (AR) is an important complication that can occur after lung transplantation and constitutes a risk factor for bronchiolitis obliterans syndrome, which is characterised by a neutrophilic airway inflammation. The specific aim of this study was to investigate the role of interleukin (IL)-17, which promotes chemotaxis of neutrophils by inducing IL-8 production, in AR.Cell differentials, mRNA and protein levels were quantified in bronchoalveolar lavages (BALs) taken from patients at 28 and 90 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 31 publications
10
129
2
Order By: Relevance
“…Although IL-17 has already been implicated in inflammatory lung disorders of humans [22][23][24][25][26], and IL-17 and/or IL-17 mRNA has been detected locally in these disorders, the presence of IL-17-containing memory Th cells has not previously been demonstrated in association with increased IL-17 production in the human lungs. The phenotype of the IL-17-containing T-cells demonstrated in the present study resembles what has previously been described for Th17 cells [7,10,27] with respect to these cells being CD4 + memory cells.…”
Section: Increase In Effector Molecules Downstream Of Il-17 and Il-22mentioning
confidence: 96%
“…Although IL-17 has already been implicated in inflammatory lung disorders of humans [22][23][24][25][26], and IL-17 and/or IL-17 mRNA has been detected locally in these disorders, the presence of IL-17-containing memory Th cells has not previously been demonstrated in association with increased IL-17 production in the human lungs. The phenotype of the IL-17-containing T-cells demonstrated in the present study resembles what has previously been described for Th17 cells [7,10,27] with respect to these cells being CD4 + memory cells.…”
Section: Increase In Effector Molecules Downstream Of Il-17 and Il-22mentioning
confidence: 96%
“…In human lung organ transplantation, IL-17 has also been reported as being elevated during acute rejection [93], while rat models have demonstrated that collagen type V-specific lymphocytes can mediate lung allograft rejection and express IL-17 locally at the site of rejection [94]. In cardiac allograft models, antagonism of the IL-17 network (via expression of an IL-17R-immunoglobin fusion protein) can reduce intragraft production of inflammatory cytokines (namely IFN-g) and prolong graft survival [95].…”
Section: Allograft Rejectionmentioning
confidence: 99%
“…13,19,20 IL-17 has important roles in bridging innate and adaptive immunity, and is involved in the host defense against extracellular pathogens, the pathophysiology of autoimmune diseases, and allograft rejection of solid organs. [21][22][23][24][25][26][27][28][29] Moreover, several reports have so far shown that Th17 cells and IL-17 has a significant impact on the development of acute GVHD in mouse models. [30][31][32][33][34][35] Recent reports have shown association of SNPs in the IL-17 gene with autoimmune diseases such as rheumatoid arthritis and ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%